Agama Sebagai Transpormasi Sosial - EKO NOPRIYANSA (El-Ghiroh : Jurnal Studi Keislaman, 2020)
Seems that the position of intellectual community gets its own attention to the public because by knowing it is expected to be able to convey an objective and neutral view in providing views on a social problem. Therefore intellectuals are characterized by their ability to respond critically to social problems through discussion or writing in the public sphere. In a wider social context, important roles as well as having the main potential in correcting social problems include religious leaders, pioneers, and intellectuals, where they have a great responsibility for a harmonious society both in religion and more in the state.